Nase zkusenosti s technikou rotace dvorce u chirurgické lécby gigantomastie - Mĕst'ák, J; Ambrozová, J; Tomásek, D; Krýslová, I (Rozhledy v chirurgii, 1994)
The authors present a less commonly used method in reduction and modelling of gigantomastia. They draw attention to the advantages of this surgical procedure which is based on rotation of the areola with a broad upper and lateral pedicle. They emphasize in particular the very good postoperative nutrition of the areolas with preservation of their sensitivity.
Keywords: Breast; Mammaplasty; hypertrofie; Nipples; ženské pohlaví; Humans; Hypertrophy; mamoplastika; prsy; Female; prsní bradavky; lidé